Scale-Up of Thin-Film Deposition-Based Solid Oxide Fuel Cell by Sputtering, a Commercially Viable Thin-Film Technology - Noh, Ho-Sung; Hong, Jongsup; Kim, Hyoungchul; Yoon, Kyung Joong; Kim, Byung-Kook; Lee, Hae-Weon; Lee, Jong-Ho; Son, Ji-Won (ELECTROCHEMICAL SOC INC, 2016)
The feasibility of fabricating large-area thin-film solid oxide fuel cells (TF-SOFC) using a commercially viable vapor deposition technology-i.e., sputtering in the present study-is investigated. By using a 2-inch sputtering system, a multi-scale-architecture platform consisting of a nanostructured NiO-yttria-stabilized zirconia (YSZ) anode and an approximately 750 nm-thick YSZ/gadolinia-doped ceria (GDC) bilayer is successfully fabricated over a 5 x 5 cm NiO-YSZ anode support. An open cell voltage (OCV) of 1.1 V and a peak power density exceeding 1.2 W cm(-2) at 600 degrees C are obtained. The total power output at 0.7 V from the 5-cm-by-5 cm TF-SOFC reaches 15.52 W at 600 degrees C and 9.76 W at 550 degrees C. The total maximum power outputs are 19.52 and 14.08 W at 600 and 550 degrees C, respectively. To our knowledge, this is the highest total power output from a vapor deposition-based SOFC. The present study demonstrates the possibility of transferring this multi-scale-architecture TF-SOFC technology to the industrial sector using commercial thin-film technologies. (C) 2016 The Electrochemical Society. All rights reserved.
Keywords: YTTRIA-STABILIZED-ZIRCONIA; PULSED-LASER DEPOSITION; CHEMICAL SOLUTION DEPOSITION; ELECTROLYTE LAYERS; SPRAY-PYROLYSIS; SOFC; TEMPERATURE; PERFORMANCE; MICROSTRUCTURE; ANODE